Zugang zu Recht 61. Junge Tagung Öffentliches Recht - Huggins, Benedikt; Herrlein, Maike; Werpers, Johanna; Brickwede, Jonas; Chatziathanasiou, Konstantin; Dudeck, Lisa; Fechter, Jonas; Fouchard, Felix; Gengenbach, Rebekka; Hennicke, Lucas; Lischewski, Isabel; Mentzel, Leonie; et al. (2021)
'Access to law' examines both personal and substantial conditions of access to the different phases of law creation and its legislative, executive and judicial manifestations. These conditions also include actual authority structures which affect threats to freedom and equality. The conference volume addresses access to legal and extrajudicial knowledge, private influence on legislation, the relationship between courts and legislatures, and access to the government and its offices. The volume discloses strategic litigation approaches and state actors' attempts to escape from legal scrutiny.